Spirituality and mental health: an analytical study in the light of the Qur’an and Sunnah = الروحانية والصحة النفسية دراسة تحليلية في ضوء القرآن والسنة - Fettane, Amar (QURAN & SUNNAH DEPARTMENT - AHAS IRKHS, 2022)
In recent years, there has been a growing awareness of the impact of modern life on psychological and mental health. With the constant demands of work, family, and the dominance of technology over human lives, many people feel overwhelmed and stressed. This can lead to a range of mental and psychological health problems, including anxiety. depression and fatigue. What added to the complexity of this problem is the diminishing of the space allocated for spirituality in human life and their submission to the manifestations and requirements of material modern life.